Wanita Wirausaha: Faktor Sukses Dan Kendala Usaha Kuliner - Yuhendri L V (Universitas Hamzanwadi, 2023)
Women have the potential to participate in economic activities as women entrepreneur. In Payakumbuh City, West Sumatra province, there has been an increase in women entrepreneurs. This indicates that they are successful in entrepreneurship, thus motivating other women to become entrepreneurs. This research aims to describe the determinants of success and obstacles factors of women entrepreneur at Payakumbuh City, West Sumatra Province.This research uses a qualitative approach with type of phenomenological research. The research informant is women entrepreneur who produces Karak Kaliang . at Payakumbuh City, West Sumatra Province, totaling 9 informants. The selection of informants is carried out by snowball sampling. This study used three data collection techniques, namely in-depth interviews, participatory observation, and documentation. Data analysis technique uses the process of qualitative research data analysis Miles, Huberman, & Saldana consisting of four activities namely data collection, data condensation, data display, and conclusion: drawing and verifyng.The results showed that the determinants of success of women entrepreneur at Payakumbuh City are family support, experience, innovation, and culture. Meanwhile, the obstacles factors are capital, raw materials, competition, place to sell products and marketing. The results of this study can be used as a guideline in increasing women's participation in economic activities as women entrepreneur to improve the economy